Identification of the earlier human-induced sedimentation change in Daya Bay, northern South China Sea using 210Pb and 137Cs. (January 2018) - Yang, Weifeng; Zhao, Xiufeng; Zhang, Fang; Fang, Ziming; Ma, Haoyang; Chen, Min; Qiu, Yusheng; Zheng, Minfang
Abstract: Over the past 30 years, the rapid development of the Chinese economy resulted in environmental problems, especially in coastal areas. To discern the effects of anthropogenic activities, 210 Pb and 137 Cs were examined in the sediment from Daya Bay, northern South China Sea. The specific activity of 137 Cs showed a clear maximum, corresponding to 1963. 210 Pb specific activity varied from 25.1 to 78.5 Bq kg − 1 . 210 Pb distribution showed a hiatus at 18–19 cm with 5–6 cm of older sediment (> 150 years), indicating direct land-originating material over a short timescale rather than natural processes. This event was attributed to the human-induced redistribution of sediment during reclamation. Based on the 137 Cs-labeled 1963 and 210 Pb-chronologies, this event was confined to late 1977, earlier than the generally recognized significant anthropogenic activities. Thus, information archived in the sediment or in records prior to the 1970s would be better environmental background in Daya Bay. Highlights: A two-stage distribution of 210 Pb was observed in a sediment core in Daya Bay. The hiatus was confined to late 1977 using 137 Cs and 210 Pb techniques. Anthropogenic perturbation was earlier than general recognition in Daya Bay.